Effectiveness Of Electronic Land Certificate Services At The Sumbawa District Land Office (Indonesia) - Rizki Asrori; Lalu Hadi Adha; Widodo Dwi Putro (Private Law, 2026)
This study aims to analyze the effectiveness of digitalizing land services at the Sumbawa Regency Land Office, specifically in terms of time efficiency, transparency, and accessibility of public services. The digitalization of land administration services is part of bureaucratic reform efforts implemented through the application of Electronic Land Certificates, as regulated by the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Regulation Number 1 of 2021. This research employs a normative legal research method using statutory and conceptual approaches. The collection of legal materials was conducted through library research involving primary, secondary, and tertiary legal sources. The findings indicate that the implementation of digitalized land services at the Sumbawa Regency Land Office has generally improved service time efficiency, enhanced transparency in administrative procedures, and increased public access to land services. The digital system allows the public to monitor service processes more openly and provides greater legal certainty regarding land rights. However, the implementation of land service digitalization still encounters several challenges, including limited information technology infrastructure, the continued use of hybrid systems that are not fully digital, issues related to land data validity, and low levels of digital literacy among certain segments of the community. Therefore, continuous efforts are necessary, including improving the quality of human resources, strengthening information technology infrastructure, and optimizing public outreach and education to enhance the overall effectiveness of land service digitalization in Sumbawa Regency.